Determination of chemical composition of Anatolian carob pod (Ceratonia siliqua L.): sugars, amino and organic acids, minerals and phenolic compounds - Ayaz, Faik Ahmet (2012)
Carob pod is the fruit of the carob tree (Ceratonia siliqua L. Fabaceae). The fruit and its products, sold both in large stores and local markets, contribute strongly to the diet of people living in the Mediterranean areas of Europe and Turkey. This study reports the composition of carob pods sampled in West and South Anatolia. Sucrose (437.3 mg/g dry weight), glucose (395.8 mg/g dry weight) and fructose (42.3 mg/g dry weight) were the major sugars identified and quantified in the fruit. Total phenolics (13.51 mg gallic acid equivalents [GAE]/g dry weight), proanthocyanidin (0.36 mg GAE/g dry weight), gallotannins (0.41 catechin equivalents [CE]/g dry weight) and flavanols (3.21 mg CE/g dry weight protein) content of the fruit were also determined. Gallic acid (3.27 mg/g dry weight) was the most abundant phenolic acid present in all three phenolic fractions (free, ester and glycoside) isolated from pods. Aspartic acid (18.25 mg/g dry weight protein) was the predominant amino acid in the pod protein fraction. Eight minerals were quantified in the fruit. Among the analyzed major minerals, K (9.70 mg/g dry weight) was the most abundant element present, and the pods were richer in Ca than in P and Mg. Levels of trace minerals were comparable to other plant species. The data are discussed in terms of the nutritional value of the carob pod.